Glucose-sensing Receptor in Pancreatic Beta-cells (Springer Singapore, 2018)
Since the 1970s, there has been much discussion about the "glucoreceptor" and "substrate site" and which of these two is the dominant theory, but new findings on the glucose-sensing receptor have now shed new light on the "glucoreceptor theory." This volume reviews recent advances concerning the glucose-sensing receptor in pancreatic beta-cells. The history of research into pancreatic beta-cells is long and complex; accordingly, the first chapters present the history of this field and explain the hypothesis of insulin secretion mechanisms: "glucoreceptor theory". Subsequent chapters examine the function and activity of the glucose-sensing receptor in pancreatic beta-cells, such as identification, channel pathway, receptor signal and physiological role. Readers will gain a thorough understanding of the glucose-sensing receptor and glucose metabolism in pancreatic beta-cells, new insights into the pathophysiology of diabetes, and learn about new targets for the treatment of diabetes. .